A Review of Eco-innovation Concept - Suziyana, Mat Dahan; Sha'ri, Mohd Yusof (2016)
Eco-innovation has been recognised as one of the essential strategy for firms to respond to the increasing global environmental issues. In this regard, the eco‐innovation concept has been an interest of scholars worldwide. Numerous studies have been carried out in their attempt to understand the concept of eco-innovation. Despite of being broadly defined in a number of diverse contexts and terminologies, they showed no general agreement on some conceptualizations of eco‐innovation. This has resulted in the emergence of very broad and unclear definitions. The meaning of eco-innovation needs to be clearly understood before embarking extensive studies on it such as the drivers and barriers of the green initiatives, the impacts of eco-innovation practice, the measurement of eco-innovation performance and many more. Sound empirical studies would depend largely on the theoretical perspectives underpinning eco-innovation. A comprehensive evaluation of concepts in eco-innovation is extremely important to enrich the sustainable innovation management field of knowledge. This paper seeks to review and assess the concept of eco-innovation. It forwards an operational definition of eco-innovation to stimulate changes in environmental innovation perception and provide clear directions for further research. The future research will use this concept to assess the performance of eco-innovation practice in a manufacturing operation.